A revision of Holothuria (Halodeima) kefersteinii (Selenka, 1867) and the revival of Holothuria inornata Semper, 1868 from sea cucumbers collected in Mexico and Central America - Honey-Escandón, Magali; Solís-Marín, Francisco A. (Zootaxa, 2018)
In 1958 Deichmann synonymized Holothuria inornata Semper, 1868 with Holothuria kefersteinii (Selenka, 1867). This nomenclature has been adopted until now. However, some specimens recently collected from the Mexican Pacific matched the original description of H. inornata Semper (1868) whereas others matched the original description by Selenka (1867). A morphological, molecular and ecological study of the specimens was conducted to confirm the identification of these specimens. The morphological characters of our specimens were compared with those contained in the original descriptions and figures of the types of both species. Besides the different color pattern of live specimens of both species, the main differences found are the presence of straight distally perforated rods in the dorsal papillae, and the presence of Holothuriophilus trapeziformis Nauck, 1880 in the cloaca of H. inornata, versus the absence of these kind of rods in the dorsal papillae, and the absence of symbionts in the cloaca in H. kefersteinii. The species identified by Deichmann (1958) as H. kefersteinii is, in fact H. inornata. Both species might have been confused because the morphology of preserved specimens is very similar and the presence of the straight rods in papillae might have been overlooked during identification. A more thorough review of the ossicles from the specimens, together with the comparison of ossicles from the type specimens, has allowed the resurrection of long-forgotten species, H. inornata